Determining the Impact of Industrial Wine Yeast Strains on Organic Acid Production Under White and Red Wine-like Fermentation Conditions - Chidi, B.S.; Rossouw, D.; Buica, A.S.; Bauer, F.F. (South African Journal of Enology and Viticulture, 2016)
Organic acids are a major contributor to wine flavour and aroma. In the past, the scientific focus has mostly been on organic acids derived from grapes or on the transformation of malic acid to lactic acid by lactic acid bacteria, since these acids contribute significantly to the final total acidity of wine. However, the organic acid concentration and composition also change significantly during alcoholic fermentation, yet only limited information regarding the impact of different yeast strains on these changes has been published. Here we report on changes in organic acid (malic, tartaric, citric, succinic, acetic and pyruvic) composition during fermentation by five widely used industrial wine yeast strains in a synthetic grape must (MS300) reflecting two very different, but both wine-like, fermentation conditions. Samples were obtained from three physiological stages during fermentation, namely the exponential growth phase (day 2), early stationary phase (day 5) and late stationary phase (day 14). These different stages were selected to provide more information on acid evolution throughout fermentation, as well as on the impact of nutritional and environmental conditions during aerobic and anaerobic fermentation. Among other observations, some strains (such as VIN13 and 285) were shown to be generally higher producers of most acids in white and/ or red wine fermentation settings, while other strains (such as DV10) were generally lower acid producers. The data clearly demonstrate that different strains have different acid consumption and production patterns, and this presents a first step towards enabling winemakers to appropriately select strains for acid management during fermentation.